Equality impact assessment - results : extension of coverage of the Freedom of Information (Scotland) Act 2002 (FOISA) to registered social landlords and their subsidiaries /: extension of coverage of the Freedom of Information (Scotland) Act 2002 (FOISA) to registered social landlords and their subsidiaries. (2019) - Scotland., Freedom of Information Unit,
No abstract available